Hospitalizations in School-Aged Children with Cerebral Palsy and Population-Based Controls. (11th May 2021) - Fortin, Olivier; Ng, Pamela; Dorais, Marc; Koclas, Louise; Pigeon, Nicole; Shevell, Michael; Oskoui, Maryam
ABSTRACT: Objective: To compare hospitalizations among children with cerebral palsy (CP) and healthy controls and to identify factors associated with hospitalizations in children with CP. Methods: This retrospective cohort study linked data from a provincial CP Registry and administrative health databases. The CP cohort was comprised of children born from 1999 to 2002. Age, sex, and region-matched controls were identified from administrative health databases. Mean differences, relative risk (RR), and 95% confidence intervals (CIs) were calculated. Results: A total of 301 children with CP were linked to administrative health data and matched to 6040 controls. Mean hospitalizations per child during the study period were higher in children with CP compared to controls (raw mean difference (RMD) 5.0 95% CI 4.7 to 5.2) with longer length of stay (RMD 2.8 95% CI 1.8 to 3.8) and number of diagnoses per hospitalization (RMD 1.6 95% CI 1.4 to 1.8). Increased risk of hospitalization was observed in non-ambulant children with CP (RR 1.12 95% CI 1.01 to 1.22) compared to ambulant children and among those with spastic tri/quadriplegic CP compared to other CP subtypes (RR 1.15, 95% CI 1.05 to 1.27). Feeding difficulties (RR 1.20 95% CI 1.13 to 1.27), cortical visual (RR 1.22 95% CI 1.13 to 1.32), cognitive (RR 1.16 95% CI 1.04 to 1.30), and communication impairment (RR 1.26 95% CI 1.10 to 1.44) were associated with increased hospitalizations. Conclusions: Children with CP face more frequent, longer hospital stays than peers, especially those with a more severe CP profile. Coordinated interdisciplinary care is needed in school-aged children with CP and medical complexity.